Electrochemically reducing α-MnO2/GO material and its application to analysing eye ointment - Hồ Xuân, Anh Vũ; Vũ, Nguyễn Văn Tuấn; Hiếu, Lê Trung; Anh, Võ Châu Ngọc; Phong, Nguyễn Hải; Đan, Hoàng Dương Thụy (Hue University Journal of Science: Natural Science, 2023)
Manganese dioxide (MnO2) was directly synthesized on a graphene oxide (GO) substrate. The electrochemical reduction process of α-MnO2/GO was investigated by using cyclic voltammetry (CV) and chronoamperometry (i-T) techniques. The obtained materials were studied by using FT-IR spectroscopy, Raman spectroscopy, surface area analysis, and electrochemical impedance spectroscopy. The α-MnO2 structure was determined through FT-IR spectroscopy and Raman spectroscopy spectra at 507 and 642.5 cm–1. The α-MnO2/ErGOCV and α-MnO2/ErGOi-T reduction materials exhibit low electrochemical impedance (0,188 and 0,147 kΩ) and a large surface area of 1.7 times greater than that of α-MnO2/GO), indicating the superior properties of the α-MnO2/ErGO composite material. These properties facilitate electron transfer and enhance the electrocatalytic activity of the sensor on the modified electrode surface. The LS-AdCSV method utilizing the α-MnO2/ErGO electrode can be employed for the simultaneous analysis of chloramphenicol and tinidazole. The chloramphenicol content in eye ointment determined with the proposed method agrees well with the labelled value.